Effect of Occupational Safety and Health, Work Environment and Compensation on Employee Performance - Nuzullaila Sitorus Pane; Kasmir Kasmir (Eduvest - Journal of Universal Studies, 2022)
Performance is the main indicator for the progress of a company, resulting in increased productivity in all parts of the system. Basically, performance is an individual thing because each individual will have a different level of performance in accordance with the values that apply to each individual. The more aspects of the job that match the individual's wishes, the higher the level of performance. This study aims to analyze the effect of occupational safety and health, work environment and compensation on employee performance. The subjects of this study were employees of PT SMG, with a population of 114 people. The data collection technique used a questionnaire instrument with a Likert scale measurement. The data were analyzed using the SmartPLS software version 3.3.7. The results of this study indicate that occupational safety and health, work environment and compensation have a significant effect on employee performance.